SUITABILITY AND PROJECTION OF LAND USE FOR GREEN OPEN SPACE IN GAMPONG TIBANG, DEAH RAYA AND ALUE NAGA SYIAH KUALA DISTRICT BANDA ACEH CITY - Dhea Asmaul Husna; Satia Negara Lubis; Agus Purwoko (Jurnal Ekonomi, 2023)
Green open space is an area that must be provided by a city, this is by the provisions in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 14 of 2022 concerning the Provision and Utilization of Green Open Space Chapter II Typology of Green Open Space Article 3 at least 30% (thirty percent) of the area of the City or Urban Area consists of public green open space of at least 20% (twenty percent) and private green open space of at least 10% (ten percent). Based on the Banda Aceh City spatial pattern plan for 2009-2029, Gampong Tibang, Alue Naga and Deah Raya are areas prioritized for green open space development. These three Gampongs have an area of 596.2 Ha, including the Tibang area of 203.3 Ha, Deah Raya 102.4 Ha and Alue Naga 290.5 Ha (BIG). These three Gampongs are located on the coast of Banda Aceh City. This research aims to analyze the extent and distribution of green open space, analyze the suitability of land use for green open space and project the need for green open space in Gampong Tibang, Deah Raya and Alue Naga, Banda Aceh City in 2033-2043. The methods used are geographic information system analysis, logical suitability matrix, projected green open space needs and descriptive. The research results show that the Gampong Tibang GOS in 2023 will have an area of 36.7 ha, the Gampong Deah Raya GOS will have an area of 28.3 ha, and Gampong Alue Naga will have an area of 44.4 ha. The suitability of the use of green open space is not appropriate based on the area of green open space in the spatial pattern plan and the existing one, Gampong Tibang, the area of green open space planned for the spatial pattern is 88.6 ha while the existing is 36.7 ha, Gampong Deah Raya, the area of green open space planned for the spatial pattern is 84.2 ha while the existing is 28, 3 ha, and Gampong Deah Raya The planned green open space area is 107.4 ha while the existing area is 44.4 ha. The projected need for green open space is based on an area of 1,227.18 ha. The projected need for green open space is based on population for 2033 with a population of 286,490 requiring green open space covering an area of 572.98 ha and in 2043 with a population of 315,525 requiring green open space covering an area of 631.05 ha.